2016
DOI: 10.1038/cddis.2016.159
|View full text |Cite
|
Sign up to set email alerts
|

PAX7 is a required target for microRNA-206-induced differentiation of fusion-negative rhabdomyosarcoma

Abstract: Rhabdomyosarcoma (RMS) is the most common soft tissue sarcoma of childhood. RMS can be parsed based on clinical outcome into two subtypes, fusion-positive RMS (FP-RMS) or fusion-negative RMS (FN-RMS) based on the presence or absence of either PAX3-FOXO1 or PAX7-FOXO1 gene fusions. In both RMS subtypes, tumor cells show histology and a gene expression pattern resembling that of developmentally arrested skeletal muscle. Differentiation therapy is an attractive approach to embryonal tumors of childhood including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 54 publications
(81 reference statements)
1
32
0
1
Order By: Relevance
“…In FP-RMS, we identified CCND2, CDK6, and ERBB3 as novel targets of miR-221. Interestingly, CCND2 is the predominant D-Type Cyclin expressed in RMS and its downregulation by miR-1/206 decreases RMS proliferation [ 34 , 55 , 56 ]. Furthermore, Cyclin D and CDK4/6 activity is tightly regulated in myoblast proliferation and differentiation [ 57 , 58 ] and overexpressed/hyperactive in cancer and RMS [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In FP-RMS, we identified CCND2, CDK6, and ERBB3 as novel targets of miR-221. Interestingly, CCND2 is the predominant D-Type Cyclin expressed in RMS and its downregulation by miR-1/206 decreases RMS proliferation [ 34 , 55 , 56 ]. Furthermore, Cyclin D and CDK4/6 activity is tightly regulated in myoblast proliferation and differentiation [ 57 , 58 ] and overexpressed/hyperactive in cancer and RMS [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cells were from the following sources: RD (CCL-136) and Rh30 (CRL-2061) from ATCC (Manassas, VA, USA), Rh3, RH4, Rh28, and Rh41 (Gerard Grosveld, St. Jude), 293T (Martine F. Roussel, St. Jude), and LHCN-M2 (Woodring Wright, University of Texas Southwestern Medical Center) [ 73 ]. Cells were authenticated with short tandem repeat profiling (Supplementary Table S2 ) [ 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…Immunoblots were performed on total cell lysates prepared in RIPA buffer as described previously (25). Blots were probed with antibodies detailed in Supplementary Table S4.…”
Section: Methodsmentioning
confidence: 99%
“…miR‐206, a member of miR‐1 family, is specifically expressed in skeletal muscle and play an important role in skeletal muscle development, function, and pathology . Furthermore, miR‐206 is involved in the pathogenesis of various diseases including pulmonary disease , heart failure , Alzheimer's disease , and various types of cancers . It is frequently downregulated in some cancer tissues, and functions as a cell cycle regulator and tumor suppressor in clear‐cell renal cell carcinoma , gastric cancer , and rhabdomyosarcoma , indicating that miR‐206 plays an important role in the development and progression of cancer .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, miR‐206 is involved in the pathogenesis of various diseases including pulmonary disease , heart failure , Alzheimer's disease , and various types of cancers . It is frequently downregulated in some cancer tissues, and functions as a cell cycle regulator and tumor suppressor in clear‐cell renal cell carcinoma , gastric cancer , and rhabdomyosarcoma , indicating that miR‐206 plays an important role in the development and progression of cancer . Previous reports have shown that miR‐206 is significantly decreased in HCC tissues, and overexpression of miRNA‐206 can promote apoptosis, induce cell cycle arrest, and inhibit proliferation, invasion, and migration of HCC cells .…”
Section: Introductionmentioning
confidence: 99%